A Telephone Triage System for Patients Calling with Symptoms of a Posterior Vitreous Detachment - Balikov, Daniel A; Zhou, Yunshu; Miller, Jason M L (Ophthalmology retina, 2023)
The purpose of the study was to develop a simple telephone questionnaire, without physical examination input, that predicts which patients calling with symptoms of a posterior vitreous detachment (PVD) have a retinal tear (RT) or rhegmatogenous retinal detachment (RD). Prospective cohort (quality improvement) study. All patients with symptoms consistent with a PVD calling a major academic ophthalmology department over a 4-month period in 2020 and who were seen on follow-up within 1.5 months (211 screened and 193 included). A comprehensive telephone questionnaire assessing for RT/RD risk factors was administered by telephone triage staff to all patients calling with symptoms of flashes, floaters, or curtain/veil in their vision. Multivariable logistic regression was used to determine risk factors most predictive of having an RT/RD during the add-on visit. Risk factor odds ratios were used to develop an RT/RD risk score. Development of a clinical risk score for having an RT/RD at the add-on visit after telephone triage. Approximately 55% of patients were previously established in the retina clinic, 26% were new to the department, 19% were previously established in the comprehensive clinic, and 7% had an RT/RD at the add-on visit. Out of 23 questions and 70 prespecified possible answers from the telephone questionnaire, the final clinical risk score for RT/RDs was derived from 7 questions and 15 possible answers. The simplified questionnaire can be administered quickly by telephone operators without any reference to physical examination or the patient's chart. The receive-operator curve for our final multivariable logistic regression and clinical risk score models have an area under the curve of > 0.90. Using a conservative clinical risk score, approximately 50% of all patients without an RT/RD can be safely seen nonurgently. Progressively higher scores can be used to determine relative urgency of an appointment. To our knowledge, this is the first study to predict risk of an RT/RD in a patient calling with symptoms consistent with a PVD without reference to the patient's physical examination or chart. Our clinical risk scoring system can be used to determine urgency of an add-on appointment and increase the number of low-risk patients with symptomatic PVDs who are scheduled routinely. The author(s) have no proprietary or commercial interest in any materials discussed in this article.